Effects of initiating moderate wine intake on abdominal adipose tissue in adults with type 2 diabetes: a 2-year randomized controlled trial. Issue 3 (3rd October 2016) - Golan, Rachel; Shelef, Ilan; Shemesh, Elad; Henkin, Yaakov; Schwarzfuchs, Dan; Gepner, Yftach; Harman-Boehm, Ilana; Witkow, Shula; Friger, Michael; Chassidim, Yoash; Liberty, Idit F; Sarusi, Benjamin; et al.
Abstract: Objective: To generate evidence-based conclusions about the effect of wine consumption on weight gain and abdominal fat accumulation and distribution in patients with type 2 diabetes. Design: In the 2-year randomized controlled CASCADE (CArdiovaSCulAr Diabetes & Ethanol) trial, patients following a Mediterranean diet were randomly assigned to drink 150 ml of mineral water, white wine or red wine with dinner for 2 years. Visceral adiposity and abdominal fat distribution were measured in a subgroup of sixty-five participants, using abdominal MRI. Setting: Ben-Gurion University of the Negev, Soroka-Medical Center and the Nuclear Research Center Negev, Israel. Subjects: Alcohol-abstaining adults with well-controlled type 2 diabetes. Results: Forty-eight participants (red wine, n 27; mineral water, n 21) who completed a second MRI measurement were included in the 2-year analysis. Similar weight losses (sd ) were observed: red wine 1·3 (3·9) kg; water 1·0 (4·2) kg ( P =0·8 between groups). Changes (95 % CI) in abdominal adipose-tissue distribution were similar: red wine, visceral adipose tissue (VAT) −3·0 (−8·0, 2·0) %, deep subcutaneous adipose tissue (DSAT) +5·2 (−1·1, 11·6) %, superficial subcutaneous adipose tissue (SSAT) −1·9 (−5·0, 1·2) %; water, VAT −3·2 (−8·9, 2·5) %, DSAT +2·9 (−2·8, 8·6) %, SSAT −0·15 (−3·3, 2·9) %. No changes in antidiabetic medication and no substantial changes in energy intake (+126 (sd 2889) kJ/d (+30·2 (sd 690) kcal/d), P =0·8) were recorded. A 2-year decrease in glycated Hb ( β =0·28, P =0·05) was associated with a decrease in VAT. Conclusions: Moderate wine consumption, as part of a Mediterranean diet, in persons with controlled diabetes did not promote weight gain or abdominal adiposity.